Hydroelectric simulation of the phreatic water response of mining cracked soil based on microbial solidification - Gao Ying; Ismail Mohd Ashraf Mohamad; Li Tao; Li Bo; Zhang Jiarui (Open Geosciences)
Coal mining in ecologically fragile areas results in the failure of aquiclude layers and the loss of surface water bodies. Herein, research was conducted on the microbial solidification of cracked soils and the corresponding response of the ecological water table. A simulation of mining-induced cracked soils was performed via microbial solidification. The mechanical and hydrological properties of cracked soil samples repaired with different filling materials were compared via unconfined compressive strength and falling head permeability tests. Hydraulic-electric similarity modeling techniques were employed to evaluate the effectiveness of microbial solidification in the aquiclude layers. After low-temperature acclimation, Bacillus megaterium adapted to the geological environment of the study area, exhibiting a high viable cell density. When the cracked soil was filled with a 1:1 ratio of aeolian sand to clay particles, the microbially remediated soil demonstrated optimal mechanical and hydraulic properties. Hydraulic-electric similarity numerical simulations revealed that the ecological water table at the coalface remained within a reasonable range following microbial solidification, suggesting that microbial solidification achieved water-preserving coal mining. These findings provide a reference for restoring aquiclude layers damaged by coal mining.